Development of bioactive patches from aloe vera and Nata De Coco for wound dressing applications - Siti Maznah, Kabeb; Nurlin, Abu Samah; Nurjannah, Salim; Farah Hanani, Zulkifli (John Wiley & Sons, Inc., 2025)
This study focuses on the development and characterization of bioactive patches derived from Aloe Vera (AV) and Nata De Coco (NDC) for advanced wound dressing applications. Utilizing the solution casting method, biocomposite films are developed using polyvinyl alcohol (PVA) with varied bio-filler content (2%−10%) w/w. Fourier-transform infrared (FTIR) analysis confirms the miscibility and compatibility of PVA and bio-fillers via intermolecular hydrogen bonding. PVA/NDC10 demonstrates the highest water-holding capacity (WHC), exhibiting an increase from 157.17% (neat PVA) to 286.01%, resulting in an 82.0% enhancement. Conversely, increasing NDC content leads to a gradual decrease in tensile strength. Notably, the hybrid biocomposite film (PVA/AV/NDC) shows a significant 20.82% improvement in tensile strength, reaching 30.79 MPa. The study underscores the promise of AV and NDC bioactive patches for advanced wound dressing. Additionally, the hybrid approach shows synergistic improvements in water retention and mechanical strength, offering a comprehensive solution for effective wound management.